Gambaran Fungsi Hormon Tiroid Pada Penderita DM Tipe 2 Rawat Jalan - Mardianto Mardianto; Suherdy Suherdy; Dharma Lindarto (Jurnal Kedokteran Syiah Kuala, 2010)
AbstractBackground:  In previous studies reported that impaired of thyroid function in patients  with type 2 diabetes showed different results. This study aims to know the description of the thyroid hormone function in  type 2 diabetes mellitus outpatient.Methods: A cross sectional  study was conducted from ·September 2009 - March 2010 in H. Adam Malik General Hospital. The subjects were all outpatients at the clinic of Endocrine and Metabolic who  met  the criteria  participated in  this study. All  samples were  examined of  TSHs, FT4, adrandom blood glucose, Total cholesterol, HDL cholesterol, and LDL cholesterol.Results:  There were 40 patients with type 2 diabetes who had participated in study with  19  men(47.5%),  and 21   women (52.5%) with  mean age of 58.3 years. We found thyroid dysfunction is10%  or 4 people and in details, 2 people (5%) of subclinical hypothyroidism and 2 people {5%) ofsubclinical hyperthyroidism. There were significant differences in average concentrations of three TSHs groups (pl  =  0.0010,  p2 =  0.012,  p3 = 0.001),  whereas Fr4    significantly different in eutiroid group and subclinical hyperthyroidism (p2 = 0.00 l) and subclinical hypothyroidism ·group and subclinical  hyperthyroidism {p3  =  0.001).   TSHs levels  correlated positively and statisticallysignificant with total cholesterol (r = 0.989, p = 0,011)Conclusions:  Overview of thyroid hormone function in 40 patients with type 2 diabetes mellitusindicates  10% of  dysfunction with  more women than men,  and ages who have been affected is over 60 years.(JKS   2010;  I: 1-8) Keywords: Dysfunction of Thyroid Hormone,  Diabetes  Mellitus Type 2